Praktik Jual Beli Melon Menggunakan Sistem Tebasan Dalam Perspektif Ekonomi Islam: (Studi Kasus Pada Petani Melon Di Desa Sendangharjo Kecamatan Brondong Kabupaten Lamongan) - Dina Afifah Nuroini; M. Aly Mahmudi (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2025)
The purpose of this study is to analyze the practice of melon buying and selling using the tebasan system in Sendangharjo Village, Brondong District, Lamongan Regency, from an Islamic economic perspective. The study used a qualitative field approach using observation, interviews, and documentation techniques. The results indicate that the tebasan system is a hereditary tradition considered practical and makes it easier for farmers to sell their crops. The transaction process is carried out through price negotiations based on land area, quantity, and quality of fruit. From an Islamic economic perspective, this practice is legitimate because it fulfills the pillars and requirements of buying and selling, and reflects the principles of justice, willingness, responsibility, and freedom from usury and gharar. However, the greater profits tend to be obtained by the person who cuts the fruit. This study confirms that the tebasan system is acceptable as long as it is implemented honestly, fairly, and transparently in accordance with sharia principles.